Conversion type positive electrode material with double-shell structure, preparation method of conversion type positive electrode material and electrochemical device
By forming a double-shell structure design of the liquid metal inner shell layer and the metal oxide outer shell layer on the surface of the conversion positive electrode material, the problems of poor rate performance and cycle capacity attenuation of the conversion positive electrode material are solved, and a positive electrode material with high energy density, excellent cycle stability and long life are achieved.
Patent Information
- Application Number
- CN202411915610.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The conversion positive electrode material has poor rate performance and severe attenuation in the short-term cycle.
A double-shell structure conversion positive electrode material is adopted, and a double-protective structure is formed by covering the liquid metal inner shell layer and the metal oxide outer shell layer on the surface of the matrix material.
It improves the capacity density, cycle stability and cycle life of the cathode material, enhances the rate performance, and is suitable for cycling conditions with high rate in a wide temperature range.
Smart Images

Figure CN119627085A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery materials, and in particular to a double-shell structure conversion-type positive electrode material, a preparation method thereof, and an electrochemical device. Background Art
[0002] In recent years, the extensive use of traditional energy sources such as fossil fuels has made environmental pollution problems more serious. Against the backdrop of rising global energy demand, the development of sustainable energy storage devices and technologies has become a top priority. Lithium-ion batteries have been widely used in portable electronic products, electric vehicles, and hybrid vehicles due to their high energy density and low cost-effectiveness. However, the current commercial intercalation-type lithium-ion battery cathodes have problems such as low energy density and rising raw material costs. Therefore, it is necessary to develop new, low-cost, high-energy-density lithium-ion battery cathode materials to meet future energy needs. Conversion-type cathode materials involve multiple electron transfer reactions during the charge and discharge process and have higher theoretical capacity. Compared with traditional intercalation-type cathode materials, the raw materials of conversion-type cathodes have high abundance of crustal elements, low cost, and are mostly environmentally friendly, so they are regarded as new cathode materials with great potential.
[0003] However, conversion-type cathode materials have poor rate performance and suffer from severe capacity decay in short-term cycles. Summary of the invention
[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a double-shell structure conversion positive electrode material.
[0005] In addition, the embodiments of the present application also provide a method for preparing the aforementioned double-shell structure conversion type positive electrode material, and an electrochemical device using the double-shell structure conversion type positive electrode material.
[0006] An embodiment of the present application provides a double-shell structure conversion positive electrode material, which includes a base material and an inner shell layer and an outer shell layer sequentially coated on the surface of the base material, wherein the base material is a conversion positive electrode material, the inner shell layer is liquid metal, and the outer shell layer is a metal oxide.
[0007] In some possible embodiments, the mass ratio of the conversion-type positive electrode material to the liquid metal is 50:(1-10).
[0008] In some possible embodiments, the mass ratio of the conversion cathode material to the metal oxide is 50:(1-5); and / or The thickness of the outer shell layer is 2nm~7nm.
[0009] In some possible embodiments, the metal oxide includes at least one of tin oxide, zinc oxide, titanium dioxide, silicon dioxide, zirconium oxide, aluminum oxide, cobalt oxide, tungsten oxide and bismuth oxide.
[0010] In some possible embodiments, the liquid metal includes at least one of gallium, gallium-tin alloy, gallium-indium alloy and gallium-indium-tin alloy.
[0011] In some possible embodiments, the conversion-type positive electrode material includes at least one of elemental sulfur, sulfide, transition metal halide, and transition metal halide / carbon composite material.
[0012] The present application also provides a method for preparing a double-shell structure conversion-type positive electrode material, comprising: Mixing a base material, a liquid metal and a dispersion medium to obtain a mixture, wherein the base material is a conversion-type positive electrode material; Physically dispersing the mixture at a temperature higher than the melting point of the liquid metal, so that the liquid metal is coated on the surface of the base material to form an inner shell layer, thereby obtaining a positive electrode material intermediate; and The cathode material intermediate is dispersed in a liquid medium containing metal elements, and a layer of metal oxide is synthesized in situ on the surface of the inner shell layer by a wet chemical synthesis method to form an outer shell layer, thereby obtaining the double-shell structure conversion cathode material.
[0013] In some possible embodiments, the liquid metal includes at least one of gallium, gallium-tin alloy, gallium-indium alloy and gallium-indium-tin alloy; and / or The mass ratio of the conversion type positive electrode material to the liquid metal is 50:(1-10).
[0014] In some possible embodiments, the physical dispersion includes at least one of planetary ball milling, high energy ball milling, ultrasonic dispersion, high speed shear dispersion, high speed grinding, mechanical stirring dispersion and high pressure homogenization dispersion; and / or The wet chemical synthesis method includes at least one of a sol-gel method, a hydrothermal method and an in-situ alcoholysis method.
[0015] In some possible embodiments, the wet chemical synthesis method is an in-situ alcoholysis method, and the reaction conditions of the in-situ alcoholysis method include: a reaction temperature of 30° C. to 60° C., a reaction time of 24 h to 48 h, and the liquid medium includes a metal organic salt and an alcohol.
[0016] In addition, an embodiment of the present application further provides an electrochemical device, including a positive electrode plate, wherein the positive electrode plate includes a positive electrode material, and the positive electrode material is the aforementioned double-shell structure conversion type positive electrode material.
[0017] Compared with the prior art, the double-shell structure conversion positive electrode material provided in the embodiment of the present application has a conversion positive electrode material as a base material, a liquid metal as an inner shell layer, and a metal oxide as an outer shell layer. First, the liquid metal in the inner shell layer has a "self-repairing" property. During the charge and discharge process, the conversion positive electrode material undergoes a volume change. The liquid metal can form an interface layer with plastic deformation capability, alleviate the volume change of the base material, and inhibit the dissolution of active substances in the base material, thereby effectively improving the capacity and cycle life of the double-shell structure conversion positive electrode material. The liquid metal can also provide electron and ion transmission channels between the base material particles, thereby improving the rate performance of the double-shell structure conversion positive electrode material. In addition, an outer shell layer of metal oxide is formed on the surface of the liquid metal, thereby limiting the large-scale movement and aggregation of the liquid metal, reducing the local aggregation of the liquid metal, and helping to maintain the stability and uniformity of the entire liquid metal inner shell layer. Through the synergistic effect of the inner shell layer and the outer shell layer, the matrix material is doubly fixed and buffered, which reduces the volume expansion of the matrix material and the loss of positive electrode active materials, and improves the interface stability of the double-shell structure conversion positive electrode material, so that the double-shell structure conversion positive electrode material exhibits ideal capacity density, excellent cycle stability and cycle life, and can be applied to wide temperature range and high-rate cycle conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A process flow chart of a method for preparing a double-shell structure conversion positive electrode material provided in one embodiment of the present application.
[0019] Figure 2 These are X-ray diffraction patterns of the double-shell structure FeF3 / carbon powder positive electrode material in Example 2 of the present application, the FeF3 / carbon powder positive electrode material in Comparative Example 1, and commercial FeF3 material.
[0020] Figure 3 This is a scanning electron microscope image of the double-shell structure FeF3 / carbon powder positive electrode material in Example 2 of the present application.
[0021] Figure 4 This is the EDS element distribution analysis diagram of the double-shell structure FeF3 / carbon powder positive electrode material in Example 2 of the present application, wherein: Figure 4 Figure a is the morphology image of the double-shell structure FeF3 / carbon powder positive electrode material. Figure 4 Figure b shows the distribution of C elements. Figure 4 The c diagram is the distribution of O elements. Figure 4 The d graph is the distribution of F elements. Figure 4 The e diagram is the distribution of Fe elements. Figure 4 The f diagram is the Ga element distribution. Figure 4 The g diagram shows the distribution of Ti elements.
[0022] Figure 5This is a rate performance diagram of a battery prepared with a double-shell structure FeF3 / carbon powder positive electrode material in Example 2 of the present application. DETAILED DESCRIPTION
[0023] The following will clearly and completely describe the technical solutions in the embodiments of the present application in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments.
[0024] Conversion-type positive electrode materials have problems such as poor rate performance and severe capacity attenuation, mainly because volume changes, unstable reaction interfaces and dissolution of positive electrode active materials are prone to occur during the charge and discharge process.
[0025] To this end, an embodiment of the present application provides a double-shell structure conversion positive electrode material, which includes a base material and an inner shell layer and an outer shell layer sequentially coated on the surface of the base material, wherein the base material is a conversion positive electrode material, the inner shell layer is liquid metal, and the outer shell layer is a metal oxide.
[0026] In the embodiment of the present application, by coating the liquid metal inner shell layer on the surface of the base material, firstly, due to the "self-repairing" property of the liquid metal, it can effectively adapt to the volume and shape changes of the base material during the charge and discharge process, and construct a coating layer that is not easy to damage and has complete mechanical structural properties, that is, it provides an interface layer that can be plastically deformed, thereby effectively alleviating the cracking and expansion problems of the positive electrode material caused by the volume change, and reducing the mechanical damage of the double-shell structure conversion type positive electrode material during the charge and discharge process. Secondly, the base material will generate some soluble metal ion intermediates during the charge and discharge process, and the liquid metal and these soluble metal ion intermediates can spontaneously alloy, so that the soluble metal ions are fixed in the inner shell structure, which inhibits the dissolution of the active substance of the positive electrode material during the charge and discharge process, thereby constructing a "dynamically stable" positive electrode interface, greatly improving the capacity density, cycle stability and cycle life of the double-shell structure conversion type positive electrode material. In addition, the liquid metal has good conductivity, and the inner shell layer, as a conductive network, can also provide electron and ion transmission channels between the base material particles, effectively improving the capacity and cycle life of the electrode.
[0027] The present application further forms a metal oxide as an outer shell on the surface of the inner shell, which is conducive to maintaining the stability and uniformity of the entire double shell structure. First, liquid metal is usually affected by the electric field, thermal effect or volume expansion during the battery charging and discharging process, and produces displacement or flow. The metal oxide outer shell can effectively "trap" the liquid metal in the inner shell, restricting the liquid metal in the inner shell from moving and gathering in a large range during the charging and discharging process, and reducing the local instability or structural damage of the inner shell caused by the movement of the liquid metal. Secondly, the metal oxide outer shell and the liquid metal inner shell have a high degree of matching in thermal expansion, which can effectively reduce the internal stress caused by temperature changes and the structural deformation caused by thermal expansion and contraction, and maintain the stability of the overall structure. The outer shell has good mechanical strength, corrosion resistance, thermal stability, and chemical stability, which helps to provide structural support, effectively reduce the cracking or damage of the inner shell due to expansion or contraction, and protect the inner shell and the matrix material from erosion by electrolytes or environmental conditions, reduce the structural damage caused by the heat generated by high temperature or electrochemical reactions in the inner shell, maintain interface stability, and maintain the overall morphology of the positive electrode material. In addition, the metal oxide shell may form a special interface effect with the liquid metal during the charge and discharge process, such as interfacial tension, which further restricts the movement and aggregation of the liquid metal. The metal oxide shell layer can also physically isolate the matrix material from the electrolyte, reduce the reaction between the positive active material in the matrix material and the electrolyte, further reduce the loss of the positive active material, and thus increase the specific capacity of the positive electrode material.
[0028] Therefore, the present application performs dual fixation and buffering of the base material through the synergistic effect of the inner shell layer and the outer shell layer. The inner shell layer that can be plastically deformed directly absorbs and buffers the volume change of the base material, and provides a conductive channel and improves the reaction activity, which is conducive to the rapid transmission of electrons and ions. The outer shell layer provides mechanical support for a second fixation and protection, which jointly reduces the volume expansion of the base material and improves the interface stability of the double-shell structure conversion positive electrode material. In addition, the double-shell structure also effectively reduces the loss of positive active materials. The synergistic effect of the inner shell layer and the outer shell layer enables the double-shell structure conversion positive electrode material to exhibit an ideal capacity density, excellent cycle stability and cycle life, and can be applied to wide temperature range and high rate cycle conditions.
[0029] The conversion type positive electrode material may include at least one of sulfur, sulfide, transition metal halide and transition metal halide / carbon composite material, etc., and has the advantages of high theoretical capacity, abundant raw materials, low cost and environmental friendliness. The conversion type positive electrode material can further be a transition metal halide / carbon composite material, and further can be a metal fluoride / carbon composite material, such as FeF3 / C composite material or CuF2 / C composite material, etc. The carbon material can build a continuous conductive network for the metal fluoride to improve the conductivity of the conversion type positive electrode material. Among them, the carbon material can be a carbon-based conductive additive, and the metal fluoride is located in the gap of the conductive structure formed by the carbon-based conductive additive material. Specifically, the carbon-based conductive additive may include but is not limited to at least one of carbon nanotubes, Super-P, acetylene black, Ketjen black carbon black, XC-72 carbon black and ordered mesoporous carbon CMK-3.
[0030] The liquid metal may include at least one of gallium, gallium-tin alloy, gallium-indium alloy and gallium-indium-tin alloy. The liquid metal has excellent electrical conductivity, high thermal conductivity and flexibility, which is conducive to further improving the electrical conductivity, safety and cycle stability of the conversion positive electrode material. In addition, the liquid metal alloy has a low melting point and good phase change characteristics, can be transformed between solid and liquid, and provides more electrochemical reaction sites, thereby improving the energy density and charge and discharge efficiency of the battery. The liquid metal may further be gallium.
[0031] The metal oxide may include at least one of tin oxide, zinc oxide, titanium dioxide, silicon dioxide, zirconium oxide, aluminum oxide, cobalt tetraoxide, tungsten oxide, and bismuth oxide. The above metal oxides have high chemical stability, good mechanical strength, and good corrosion resistance, and can effectively extend the service life of the double-shell structure conversion positive electrode material. In addition, the above metal oxides have excellent thermal stability and a high melting point, and can remain stable in a high temperature environment, reducing the risk of thermal runaway. The metal oxide may further be at least one of titanium dioxide and silicon dioxide.
[0032] In some embodiments, the mass ratio of the conversion cathode material to the liquid metal can be 50: (1-10). Adding an appropriate amount of liquid metal can form an effective and uniformly coated inner shell layer on the surface of the material, further improving the energy density and cycle performance of the cathode material. Exemplarily, it can be 50: 1, 50: 2, 50: 3, 50: 4, 50: 5, 50: 6, 50: 7, 50: 8, 50: 9, 50: 10 or any value within the range of any two of the above values. The mass ratio can further be 50: (3-6).
[0033] In some embodiments, the mass ratio of the conversion cathode material to the metal oxide can be 50:(1-5). The mass ratio in the above range is conducive to providing the metal oxide outer shell layer with sufficient structural strength and chemical stability, while also giving full play to the high energy storage capacity of the conversion cathode material. Exemplarily, it can be 50:1, 50:2, 50:3, 50:4, 50:5 or any value within the range of values composed of any two of the above values. The mass ratio can further be 50:(2-4).
[0034] In some embodiments, the thickness of the outer shell layer can be 2nm to 7nm, which can effectively limit the large-scale movement and aggregation of liquid metal, and effectively improve the structural stability and chemical stability of the double-shell structure conversion positive electrode material. The thickness of the outer shell layer can be 2nm, 3nm, 4nm, 5nm, 6nm, 7nm or any value within the numerical range composed of any two of the above values. The thickness of the outer shell layer can further be 3nm to 5nm.
[0035] It can be understood that in addition to conversion-type positive electrode materials, the modification method using liquid metal and metal oxide double shells in the present application can be used for other lithium-ion battery electrode materials with large volume changes during charging and discharging, such as silicon-based negative electrode materials, etc., which can effectively alleviate the capacity attenuation and electrode failure problems caused by volume expansion.
[0036] Compared with the prior art, the double-shell structure conversion positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. The double-shell structure conversion positive electrode material provided in the embodiment of the present application sequentially forms an inner shell layer and an outer shell layer on the surface of the base material. The inner shell layer provides an interface layer with plastic deformation ability, which effectively alleviates the volume expansion of the base material and inhibits the dissolution of the active substance in the base material. At the same time, the outer shell layer restricts the large-scale movement and aggregation of the liquid metal, maintaining the stability and uniformity of the entire inner shell layer. The double-shell structure synergistically fixes and buffers the base material, so that the double-shell structure conversion positive electrode material exhibits ideal capacity density, rate performance, cycle stability and cycle life, and can be applied to high-rate cycle conditions in a wide temperature range.
[0037] 2. By adjusting the mass ratio of the conversion cathode material, liquid metal and metal oxide in the double-shell structure conversion cathode material, it is beneficial to regulate the energy density, cycle performance and structural stability of the double-shell structure conversion cathode material at a high level.
[0038] See also Figure 1 As shown, based on the same inventive concept, the preparation method of the double-shell structure conversion positive electrode material provided in the embodiment of the present application specifically includes the following steps: Step S1, mixing a base material, a liquid metal and a dispersion medium to obtain a mixture, wherein the base material is a conversion-type positive electrode material.
[0039] Specifically, in a glove box, a certain mass ratio of conversion-type cathode material and liquid metal are added into a container, and an appropriate amount of dispersion medium is added into the container to obtain a mixture.
[0040] The conversion type positive electrode material may include at least one of elemental sulfur, sulfide, transition metal halide, and transition metal halide / carbon composite material, etc. The conversion type positive electrode material may further be transition metal fluoride and transition metal fluoride / carbon composite material.
[0041] The liquid metal may include at least one of gallium, a gallium-tin alloy, a gallium-indium alloy, and a gallium-indium-tin alloy. The liquid metal may further be gallium.
[0042] In some embodiments, the mass ratio of the conversion cathode material to the liquid metal can be 50: (1-10). The mass ratio in the above range is conducive to coating the surface of the conversion cathode material with an appropriate amount of liquid metal to form a complete and continuous coating layer to inhibit the dissolution of the cathode active material, while not affecting the lithium ion transmission efficiency, thereby balancing the energy density and cycle performance of the double-shell structure conversion cathode material. Exemplarily, it can be 50: 1, 50: 2, 50: 3, 50: 4, 50: 5, 50: 6, 50: 7, 50: 8, 50: 9, 50: 10 or any value within the range of any two of the above values. The mass ratio can further be 50: (2-5).
[0043] The dispersion medium can be an organic solvent that does not react with the conversion positive electrode material and the liquid metal. The dispersion medium helps to uniformly mix and effectively disperse the liquid metal and the conversion positive electrode material, while providing an inert environment to prevent reaction interference and improve the coating effect. Exemplarily, the dispersion medium can be a liquid dispersion medium, including at least one of anhydrous ethanol, anhydrous acetonitrile, N-methylpyrrolidone, acetone, N,N-dimethylformamide, isopropanol, ethylene glycol dimethyl ether, toluene, ethylene glycol, propylene glycol and dimethyl sulfoxide. Further, the dispersion medium can include at least one of anhydrous ethanol, anhydrous acetonitrile, N-methylpyrrolidone and acetone.
[0044] In some embodiments, the preparation of transition metal fluoride / carbon composite materials in the conversion cathode material, taking FeF3 / C and CuF2 / C as examples, can be: First, a certain concentration of iron source or copper source solution is prepared, and a certain amount of carbon source is added to the solution. At this time, ultrasonic technology can be used to promote dispersion to obtain a mixture; then, the mixture is dried and heated in a fluorine source gas atmosphere for fluorination to obtain the FeF3 / C or CuF2 / C composite material.
[0045] Alternatively, FeF3 or CuF2 and a carbon source may be directly subjected to physical dispersion treatment (such as ball milling) to obtain the FeF3 / C or CuF2 / C composite material.
[0046] Step S2, physically dispersing the mixture at a temperature higher than the melting point of the liquid metal, so that the liquid metal is coated on the surface of the base material to form an inner shell layer, thereby obtaining a positive electrode material intermediate.
[0047] Specifically, after the mixture obtained in step S1 is physically dispersed at a temperature higher than the melting point of the liquid metal, the sample that has undergone the above-mentioned physical dispersion treatment is transferred to a drying device and dried in a drying environment at a certain temperature, so that the liquid metal is fully coated on the surface of the matrix material particles to form an inner shell layer, thereby obtaining a positive electrode material intermediate coated with a liquid metal inner shell layer.
[0048] In this step, after physical dispersion and drying treatment, the liquid metal particles are evenly wrapped on the outside of the matrix material, and there is a certain physical adsorption force between the liquid metal particles and the surface of the matrix material, so that the liquid metal particles are fixed on the surface of the matrix material to form a layer of liquid metal coating on the surface of the matrix material, that is, the inner shell layer in the double-shell structure conversion positive electrode material. The liquid metal can provide an interface layer capable of plastic deformation, effectively alleviate the volume expansion of the conversion positive electrode material, and can also provide an electron and ion transmission channel for the conversion positive electrode material, thereby improving the capacity and cycle life of the double-shell structure conversion positive electrode material.
[0049] In this step, physical dispersion is used to break the liquid metal from the macroscopic droplet state into nano-scale microscopic droplets with the help of external shear and impact mechanical energy, so that it is evenly distributed in the dispersion medium; on the other hand, mechanical force causes the liquid metal microscopic droplets to fully contact with the conversion positive electrode material particles, generating force interaction, ensuring that the liquid metal effectively coats the surface of the conversion positive electrode material particles. Compared with the chemical dispersion method, the physical dispersion method has low cost and simple operation, and is more suitable for the preparation method of the double-shell structure conversion positive electrode material in this application.
[0050] In some embodiments, physical dispersion may include at least one of planetary ball milling, high energy ball milling, ultrasonic dispersion, high speed shear dispersion, high speed grinding, mechanical stirring dispersion, and high pressure homogenization dispersion. Physical dispersion may further include at least one of planetary ball milling, high energy ball milling, ultrasonic dispersion, and high speed shear dispersion. It is understood that physical dispersion includes but is not limited to the above methods, and any method that can meet the requirement of sufficient dispersion is acceptable.
[0051] In some embodiments, the conditions for the drying process may include: a temperature of 70°C to 120°C, a time of 6h to 12h, and a vacuum environment. The drying equipment may be a vacuum oven. During the drying process, the liquid metal can more evenly expand and penetrate into the surface of the matrix material particles, and effectively remove moisture or other volatile impurities that may be present in the mixture. The vacuum environment can also reduce the formation of bubbles, forming a continuous and complete inner shell layer, thereby improving the overall stability and electrochemical properties of the material. The temperature may be 70°C, 80°C, 90°C, 100°C, 110°C, 120°C or any value within the numerical range composed of any two of the above values, and may further be 80°C to 100°C. The time may be 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value within the numerical range composed of any two of the above values, and may further be 8h to 10h.
[0052] Step S3, dispersing the cathode material intermediate in a liquid medium containing metal elements, and synthesizing a layer of metal oxide in situ on the surface of the inner shell layer by a wet chemical synthesis method to form an outer shell layer, thereby obtaining a double-shell structure conversion cathode material.
[0053] Specifically, the cathode material intermediate is dispersed in a liquid medium containing metal elements, a layer of metal oxide is synthesized in situ on the surface of the inner shell layer by a wet chemical synthesis method, and then solid precipitation separation and drying treatment are performed to obtain a double-shell structure conversion cathode material.
[0054] Among them, the wet chemical synthesis method can realize the in-situ synthesis of the metal oxide layer under mild conditions, which is conducive to controlling the thickness, uniformity and tightness of the outer shell layer with the inner shell layer, as well as the composition and morphology of the metal oxide, thereby improving the structural stability and electrochemical performance of the double-shell structure conversion positive electrode material. Secondly, compared with the high-temperature solid phase method, the wet chemical synthesis method is simple to operate, has low energy consumption, low cost, and is easy to achieve large-scale production.
[0055] In some embodiments, the wet chemical synthesis method may include at least one of a sol-gel method, a hydrothermal method, and an in-situ alcoholysis method.
[0056] Furthermore, the wet chemical synthesis method can adopt an in-situ alcoholysis method, in which the liquid medium includes a metal organic salt and an alcohol. The in-situ alcoholysis method can promote the hydrolysis and polycondensation reaction of the metal organic salt under mild conditions through the action of an alcohol solvent, thereby uniformly growing a layer of metal oxide, i.e., an outer shell layer, on the surface of the inner shell layer. In addition, the alcoholysis process also helps to obtain a uniform and firm metal oxide layer, reduces the problem of unevenness or easy shedding of the outer shell layer, and also enhances the adhesion between the inner shell layer and the matrix material, thereby improving the overall stability of the double shell structure.
[0057] The reaction conditions of the in-situ alcoholysis method may include: (i) the reaction temperature is 30°C to 60°C, and high temperature treatment is not required, which helps to reduce energy consumption and reduce the adverse effects of high temperature on the double-shell structure conversion positive electrode material, especially effectively protecting the stability of the liquid metal. The reaction temperature can be 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C or any value within the numerical range composed of any two of the above values. The reaction temperature can further be 40°C to 50°C. (ii) The reaction time is 24h to 48h, which is conducive to the full progress of the reaction. The reaction time can be 24h, 30h, 36h, 42h, 48h or any value within the numerical range composed of any two of the above values. The reaction time can further be 24h to 36h.
[0058] The liquid medium used includes a metal organic salt and an alcohol, and can further be a mixed solution containing only a metal organic salt and an alcohol, wherein the metal organic salt can include at least one of tetrabutyl titanate, titanium isopropoxide, tetraethoxysilane, tetraethyl vanadate, triisobutyl aluminum, and zirconium n-butoxide, etc. The alcohol can include at least one of methanol, ethanol, isopropanol, butanol, cyclohexanol, glycerol, ethylene glycol, and propylene glycol, etc.
[0059] The ratio of the metal organic salt to the cathode material intermediate in the liquid medium can be (0.1-0.4) mol: 1 g, which is conducive to the formation of an appropriate amount of metal oxide. The ratio can be 0.1 mol: 1 g, 0.2 mol: 1 g, 0.3 mol: 1 g, 0.4 mol: 1 g or any value within the numerical range composed of any two of the above values. The ratio can further be (0.2-0.4) mol: 1 g.
[0060] In the above liquid medium, the ratio of the metal organic salt to the alcohol can be (0.05-0.1) mol: 1L, and the above ratio can control the generation rate of the metal oxide to be moderate. For example, it can be 0.05 mol: 1L, 0.06 mol: 1L, 0.07 mol: 1L, 0.08 mol: 1L, 0.08 mol: 1L, 0.1 mol: 1L or any value within the numerical range composed of any two of the above values. The ratio can further be (0.06-0.08) mol: 1L.
[0061] In some embodiments, the conditions for the drying process may include: a temperature of 70°C to 120°C, a time of 6h to 12h, and a vacuum environment. The drying equipment may be a vacuum oven. During the drying process, the above temperature and vacuum environment are conducive to the formation of a continuous and complete outer shell layer, thereby improving the overall stability and electrochemical performance of the double-shell structure conversion positive electrode material. The temperature may be 70°C, 80°C, 90°C, 100°C, 110°C, 120°C or any value within the numerical range composed of any two of the above values, and may further be 80°C to 100°C. The time may be 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value within the numerical range composed of any two of the above values, and may further be 8h to 10h.
[0062] Compared with the prior art, the preparation method of the double-shell structure conversion positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. The physical dispersion method is used to first coat a layer of liquid metal on the surface of the conversion positive electrode material, providing the conversion positive electrode material with an inner shell layer with plastic deformation ability, effectively alleviating the volume expansion of the conversion positive electrode material. The physical dispersion method has the advantages of high efficiency and low cost, and is suitable for the preparation method of this application.
[0063] 2. The wet chemical synthesis method is used to in-situ synthesize a metal oxide outer shell layer on the surface of the inner shell layer, which helps to reduce the large-scale movement and uneven aggregation of liquid metal in the inner shell layer, and enhance the structural stability and chemical stability of the double-shell structure conversion cathode material. The wet chemical synthesis method is easy to control the metal oxide layer generation process, simple to operate, low energy consumption, low cost, and easy to achieve large-scale production.
[0064] 3. This preparation method is simple, efficient, and low-cost, which is conducive to the large-scale production of double-shell structure conversion positive electrode materials and has excellent commercial prospects.
[0065] The embodiment of the present application also provides an electrochemical device (such as a lithium-ion battery), which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate includes a positive electrode material, and the positive electrode material is a double-shell structure conversion type positive electrode material as described above. The electrochemical device prepared using the double-shell structure conversion type positive electrode material can give full play to the advantages of the high energy density of the double-shell structure conversion type positive electrode material, and at the same time has good cycle stability and cycle life, and can be applied to the field of high-rate cycle in a wide temperature range.
[0066] Among them, the negative electrode plate can be a lithium plate. The electrolyte can be a local high concentration electrolyte, including a lithium salt, an ether solvent and a fluorine-containing diluent. Exemplarily, the lithium salt in the electrolyte is a lithium salt of bis(fluorosulfonyl)imide, the ether solvent is ethylene glycol dimethyl ether, and the fluorine-containing diluent is bis(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and fluorobenzene. The above wide temperature range can be between -20°C and 45°C, and the rate range is between 0.1C and 10C.
[0067] The above-mentioned double-shell structure conversion positive electrode material, its preparation method and electrochemical device are further described below through specific embodiments.
[0068] Example 1 Step S1: In a glove box, 1000 mg of FeF2 / carbon composite material (conversion-type positive electrode material) and 100 mg of liquid metal gallium are added to a sealed ball mill, and 10 mL of N-methylpyrrolidone is added to the ball mill to obtain a mixture.
[0069] Step S2: ball mill the mixture at 350 rpm for 5 h to fully coat the surface of the FeF2 / carbon composite material particles with liquid metal gallium. The slurry after ball milling is transferred to a vacuum oven, slowly evacuated to remove bubbles, and then dried in a drying environment at a drying temperature of 105° C. for 8 h to obtain a FeF2 / carbon composite material coated with liquid metal, i.e., a positive electrode material intermediate.
[0070] Step S3, take 100 mg of the positive electrode material intermediate and disperse it in 20 mL of anhydrous ethanol, then add 20 mmol of tetrabutyl titanate, put it into an ultrasonic cleaner for ultrasonic dispersion for 30 minutes, stir it at 50 ° C for 24 hours for in-situ alcoholysis reaction, and in-situ generate a titanium dioxide coating layer on the surface of the positive electrode material intermediate. The above sample is centrifuged and separated into a precipitate, and then transferred to a vacuum oven and dried in a drying environment at a drying temperature of 105 ° C for 8 hours; after the sample is dried and cooled to room temperature, a double-shell structure conversion positive electrode material (double-shell structure FeF2 / carbon powder positive electrode material) is obtained, which is transferred to a glove box environment for storage.
[0071] Step S4, using double-shell structure FeF2 / carbon powder material as the positive electrode material of the lithium-ion battery, lithium sheet as the negative electrode material, 10mmol of bis(fluorosulfonyl)imide lithium salt dissolved in 10mL ethylene glycol dimethyl ether and 36mL bis(2,2,2-trifluoroethyl) ether solvent as the secondary electrolyte, and assembling a battery.
[0072] Example 2 The difference from Example 1 is that in step S1, the conversion-type positive electrode material is selected as FeF3 / carbon composite material. The other steps are basically the same as Example 1, please refer to Example 1.
[0073] Example 3 The difference from Example 1 is that in step S1, the conversion-type positive electrode material is selected as CuF2 / carbon composite material. The other steps are basically the same as those in Example 1, please refer to Example 1.
[0074] Example 4 The difference from Example 2 is that in step S1, the mass of liquid metal gallium added is 50 mg; in step S3, the amount of tetrabutyl titanate added is 40 mmol. The other steps are basically the same as Example 2, please refer to Example 2.
[0075] Comparative Example 1 The same FeF3 / carbon composite material as in Example 2, but without the double-shell structure, was used as the positive electrode material of a lithium-ion battery, a lithium sheet was used as the negative electrode material, and 10 mmol of bis(fluorosulfonyl)imide lithium salt was dissolved in 10 mL of ethylene glycol dimethyl ether and 36 mL of bis(2,2,2-trifluoroethyl) ether solvent as the secondary electrolyte to assemble a battery.
[0076] The double-shell structure conversion-type cathode materials and batteries obtained in Examples 1-4 and Comparative Example 1 were subjected to the following tests.
[0077] 1. X-ray diffraction test to observe the crystal structure and element existence form of the positive electrode material.
[0078] 2. Scanning electron microscope observation to observe the existence form of the positive electrode material.
[0079] 3. EDS mapping (energy dispersive X-ray spectroscopy mapping) is used to observe the surface morphology of the positive electrode material and the distribution of elements in the positive electrode material.
[0080] 4. High and low temperature rate performance test: The battery rate performance was tested using current densities of 0.5C, 1C, 2C, 5C, and 0.5C in sequence. Each current density was cycled 10 times. 1C was defined as 719mAh / g. Rate cycles were performed at low temperature of 0℃, room temperature of 25℃, and high temperature of 40℃.
[0081] The above test results show: like Figure 2 As shown in FIG. 1 , compared with the commercial FeF3 material and comparative example 1, the X-ray diffraction results of the double-shell structure FeF3 / carbon positive electrode material prepared in Example 2 show that Example 2 maintains the crystal structure of FeF3, and the gallium and TiO2 in the double-shell structure FeF3 / carbon positive electrode material exist in an amorphous state, which is conducive to alleviating the volume expansion of the FeF3 / carbon positive electrode material. At the same time, scanning electron microscopy and EDS mapping were performed on Example 2, and the test results are shown as follows: Figure 3 and Figure 4 As shown. Figure 3 It can be seen that the double-shell structure FeF3 / carbon cathode material exists in the form of nanoparticles. Figure 4 It can be seen that the gallium element in the inner shell and the Ti element in the outer shell are evenly distributed on the surface of the FeF3 / carbon particles, indicating that the double-shell structure is evenly coated on the surface of the conversion positive electrode material.
[0082] The rate performance of the button cell with double shell structure FeF3 / carbon positive electrode material prepared in Example 2 is as follows: Figure 5 As shown, the high and low temperature rate performance test was carried out in the voltage range of 1.1~4.0V by testing with a CR2032 button battery: the double-shell structure FeF3 / carbon positive electrode material showed good rate performance at 0℃, 25℃ and 40℃. At low temperature of 0℃ and high rate of 5C, the discharge capacity of about 250mAh / g was still maintained. Comparative Example 1 under the same conditions was tested with a CR2032 button battery. At 0℃, the battery could not be recharged after the first discharge. The test results show that when the double-shell structure FeF3 / carbon positive electrode material is used in lithium-ion batteries, under high-rate cycling conditions in a wide temperature range, it shows an ideal capacity density, excellent cycle stability and capacity retention rate compared to products that have not been modified by double-shell structure coating.
[0083] It can be seen that the synergistic effect of the double-shell structure double-fixes and buffers the matrix material, that is, the conversion-type positive electrode material, so that the double-shell structure conversion-type positive electrode material exhibits ideal capacity density, rate performance, excellent cycle stability and cycle life, and can be applied to high-rate cycle conditions in a wide temperature range.
[0084] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A double-shell structure conversion positive electrode material, characterized in that: It comprises a base material and an inner shell layer and an outer shell layer which are sequentially coated on the surface of the base material, wherein the base material is a conversion-type positive electrode material, the inner shell layer is liquid metal, and the outer shell layer is a metal oxide.
2. The double-shell structure conversion positive electrode material according to claim 1, characterized in that: The mass ratio of the conversion type positive electrode material to the liquid metal is 50:(1-10).
3. The double-shell structure conversion positive electrode material according to claim 1, characterized in that: The mass ratio of the conversion positive electrode material to the metal oxide is 50:(1-5); and / or The thickness of the outer shell layer is 2nm~7nm.
4. The double-shell structure conversion positive electrode material according to claim 1, characterized in that: The liquid metal comprises at least one of gallium, gallium-tin alloy, gallium-indium alloy and gallium-indium-tin alloy; and / or The metal oxide includes at least one of tin oxide, zinc oxide, titanium dioxide, silicon dioxide, zirconium oxide, aluminum oxide, cobalt oxide, tungsten oxide and bismuth oxide.
5. The double-shell structure conversion positive electrode material according to claim 1, characterized in that: The conversion-type positive electrode material includes at least one of elemental sulfur, sulfide, transition metal halide and transition metal halide / carbon composite material.
6. A method for preparing a double-shell structure conversion positive electrode material, characterized in that: include: Mixing a base material, a liquid metal and a dispersion medium to obtain a mixture, wherein the base material is a conversion-type positive electrode material; Physically dispersing the mixture at a temperature higher than the melting point of the liquid metal, so that the liquid metal is coated on the surface of the base material to form an inner shell layer, thereby obtaining a positive electrode material intermediate; and The cathode material intermediate is dispersed in a liquid medium containing metal elements, and a layer of metal oxide is synthesized in situ on the surface of the inner shell layer by a wet chemical synthesis method to form an outer shell layer, thereby obtaining the double-shell structure conversion cathode material.
7. The method for preparing a double-shell structure conversion positive electrode material according to claim 6, characterized in that: The liquid metal comprises at least one of gallium, gallium-tin alloy, gallium-indium alloy and gallium-indium-tin alloy; and / or The mass ratio of the conversion type positive electrode material to the liquid metal is 50:(1-10).
8. The method for preparing a double-shell structure conversion type positive electrode material according to claim 6, characterized in that: The physical dispersion includes at least one of planetary ball milling, high-energy ball milling, ultrasonic dispersion, high-speed shear dispersion, high-speed grinding, mechanical stirring dispersion and high-pressure homogenization dispersion; and / or The wet chemical synthesis method includes at least one of a sol-gel method, a hydrothermal method and an in-situ alcoholysis method.
9. The method for preparing a double-shell structure conversion positive electrode material according to claim 8, characterized in that: The wet chemical synthesis method is an in-situ alcoholysis method, and the reaction conditions of the in-situ alcoholysis method include: a reaction temperature of 30° C. to 60° C., a reaction time of 24 h to 48 h, and the liquid medium includes a metal organic salt and an alcohol.
10. An electrochemical device, characterized in that: It includes a positive electrode plate, wherein the positive electrode plate includes a positive electrode material, and the positive electrode material is a double-shell structure conversion type positive electrode material as described in any one of claims 1 to 5 or a double-shell structure conversion type positive electrode material prepared by the preparation method of the double-shell structure conversion type positive electrode material as described in any one of claims 6 to 9.
Citation Information
Patent Citations
Liquid metal-lithium manganous silicate shell-core structured lithium battery positive electrode material and preparation method thereof
CN106920933A
Liquid metal / oxide lithium-sulfur battery positive electrode material
CN113113607A
Liquid metal coated and modified metal fluoride positive electrode material and preparation method thereof
CN116487581A